2019
DOI: 10.19166/derema.v14i1.1367
|View full text |Cite
|
Sign up to set email alerts
|

Sharing Economy: A Study on the Factors Influencing Users' Motivation to Use Ride Sharing Platforms

Abstract: <p>This research is intended to explore sharing economy, particularly ride sharing. The study aims to identify the impact of four factors—economic, social, environmental, and technological—on individuals' motivation and decision to use three ride sharing platforms: UBER, GRAB and Go-JEK in Indonesia. Based on available literature, four research hypotheses are tested, namely that (1) economic factors; (2) social factors;(3)  environmental factors; and (4) technological factors have positive influence on i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…Given the novelty of the concept of the sharing economy, it is not surprising that a Pew Research Center report from May 2016 found that 73 percent of Americans were unfamiliar with the term "sharing economy", the Pew survey included buying second-hand goods on sites such as eBay and Craigslist (both founded in 1995) in their definition of the sharing economy [15]. The definition of sharing economy may be commenced by interpreting the word "share" as follows: "a portion belonging to, due to, or contributed by an individual or group; one's full or fair portion; and the part allotted or belonging to one of a number owning together property or interest " [16]. Sharing economy is also referred to by other terms, for example: collaborative, sharing consumption, collaborative economy, on-demand economy, peer-to-peer economy, zero marginal cost economy, and crowd-based capitalism [17], we consider the sharing economy as an umbrella concept that encompasses several ICT developments and technologies [1], and the sharing economy phenomenon is not only a commodity or services market prerogative [18].…”
Section: Background 21 Understanding Sharing Economymentioning
confidence: 99%
See 4 more Smart Citations
“…Given the novelty of the concept of the sharing economy, it is not surprising that a Pew Research Center report from May 2016 found that 73 percent of Americans were unfamiliar with the term "sharing economy", the Pew survey included buying second-hand goods on sites such as eBay and Craigslist (both founded in 1995) in their definition of the sharing economy [15]. The definition of sharing economy may be commenced by interpreting the word "share" as follows: "a portion belonging to, due to, or contributed by an individual or group; one's full or fair portion; and the part allotted or belonging to one of a number owning together property or interest " [16]. Sharing economy is also referred to by other terms, for example: collaborative, sharing consumption, collaborative economy, on-demand economy, peer-to-peer economy, zero marginal cost economy, and crowd-based capitalism [17], we consider the sharing economy as an umbrella concept that encompasses several ICT developments and technologies [1], and the sharing economy phenomenon is not only a commodity or services market prerogative [18].…”
Section: Background 21 Understanding Sharing Economymentioning
confidence: 99%
“…Motivation can be defined as something that can encourage someone to undertake or not undertake an action, more specifically, defines motivation as a process for initiating, directing, and maintaining the achievement of an objective influenced by biological, emotional, social, and cognitive factors. From this definition, in the context of economic and business behavior, then motivation can be interpreted as an individual action to start (decide) to use or not use something to meet needs [16].…”
Section: Determinants Of Sharing Economy 221 Motivation and Decisionmentioning
confidence: 99%
See 3 more Smart Citations